A hypothetical comparative evaluation system for arctic indoors - Seyed-Amin Tabatabaeifard; Jean-François Lalonde; Marc Hébert; André Potvin; Claude MH. Demers (Frontiers of Architectural Research)
This research presents an innovative approach to evaluating indoor spaces, combining qualitative attributes with numerical architectural metrics. A hypothetical comparative visualization system is introduced, utilizing HDR visual imaging and thermal imaging in 360° field of view across multiple indoor environments. The study aims to provide architects and occupants with a user-friendly tool informing them about the primary considerations of their built spaces, with a specific focus on indoor environmental qualities in remote Arctic regions. Key inquiries delve into the efficacy of the spherical approach and the capacity of comparative visualization to offer insights into space quality. Preliminary experiments contrast indoor environments in terms of circadian lighting, thermal uniformity, and view access to outside in the 360° field of view (VAR360). The resulting visualizations hold significance in introducing an immersive approach for depicting specific non-visible environmental qualities, particularly in relation to the window characteristics of spaces. It demonstrates the integration of multiple environmental variables, both steady-state and temporal, from central points within spaces, providing a comprehensive view over their non-visible qualities. These results should be useful for researchers and practitioners within building sciences, computer vision, and photobiology, showcasing an out-of-the-box approach for categorizing indoor spaces based on standards and human-environmental qualifications.